PENGARUH BRAND EQUITY TERHADAP LOYALITAS PELANGGAN PADA PRODUK YOGURT FRESHTIME - Agrivinie Rainy Firohmatillah; Muhammad Verlyansyah (Fakultas Pertanian Universitas Mataram, 2026)
This research aims to determine the level of Freshtime’s Brand Equity, the influence of each dimension of Brand Equity on Customer Loyalty both partially and simultaneously and the efforts that can be made to improve Freshtime’s Brand Equity and Customer Loyalty. The research method used is a quantitative method using a descriptive approach. The sample in this research amounted to 100 respondents who were selected by combining two techniques namely Accidental and Purposive Sampling. The analytical method used is Multiple Linier Regression Analysis using statistical tool SPSS version 26. The result of this study shows that Freshtime’s Brand Equity level falls into the high category. The data analysis results using Multiple Linier Regression test show that Brand Awareness, Brand Association, Perceived Quality and Brand Loyalty have a significant partial effect on Customer Loyalty. Meanwhile, Brand Equity also has a significant simultaneous effect on Customer Loyalty.